Guidelines for the treatment of severe acute malnutrition: a systematic review of the evidence for antimicrobial therapy - Williams, P; Berkley, J (Taylor and Francis, 2018)
Abstract: Severe acute malnutrition (SAM) affects nearly twenty million children and is responsible for up to one million deaths per year in children under the age of five years. The current WHO guidelines recommend oral amoxicillin for children with uncomplicated malnutrition and parenteral benzylpenicillin and gentamicin for children with complicated malnutrition, although the administration of empirical antibiotics for children with SAM has recently been debated in the literature in light of cost pressures and increasing antimicrobial resistance (AMR) worldwide. METHODS: We conducted a systematic review of the current published literature assessing the efficacy, safety, cost effectiveness and pharmacokinetics of antimicrobial treatment of children with SAM, in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). RESULTS: The initial search produced 712 papers, of which eight met the inclusion criteria. Quality assessment of the studies was performed as per the Grading of Recommendations Assessment, Development and Evaluation (GRADE) guidelines.34 International guidelines and clinical data registries were also reviewed, revealing inconsistencies in current first- and second-line therapies and dosing regimens. INTERPRETATION: The current evidence supports the continued use of broad-spectrum oral amoxicillin for treating children as outpatients with uncomplicated SAM. There is no strong evidence base to change the current parenteral therapy guidelines for children admitted with complicated SAM, although they should be clarified to harmonise the dosage regiment of amoxicillin for the treatment of SAM to 40mg/kg twice daily, and to continue parenteral antimicrobials beyond 2 days if indicated by the clinical condition.